2013
DOI: 10.1186/1471-2156-14-84
|View full text |Cite
|
Sign up to set email alerts
|

Peach genetic resources: diversity, population structure and linkage disequilibrium

Abstract: BackgroundPeach (Prunus persica (L.) Batsch) is one of the most important model fruits in the Rosaceae family. Native to the west of China, where peach has been domesticated for more than 4,000 years, its cultivation spread from China to Persia, Mediterranean countries and to America. Chinese peach has had a major impact on international peach breeding programs due to its high genetic diversity. In this research, we used 48 highly polymorphic SSRs, distributed over the peach genome, to investigate the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 55 publications
9
86
3
Order By: Relevance
“…The rapid decay of LD in the wild and primitive diversity groups of cacao and the slow or non-existent decay in cultivated groups (Fig. 2) resemble similar patterns observed for peach (Li et al 2013) and cherry (Arunyawat et al 2012). In contrast, wild and cultivated varieties of grapevine exhibit very similar patterns of genome-wide LD (Myles et al 2011).…”
Section: Discussionmentioning
confidence: 52%
“…The rapid decay of LD in the wild and primitive diversity groups of cacao and the slow or non-existent decay in cultivated groups (Fig. 2) resemble similar patterns observed for peach (Li et al 2013) and cherry (Arunyawat et al 2012). In contrast, wild and cultivated varieties of grapevine exhibit very similar patterns of genome-wide LD (Myles et al 2011).…”
Section: Discussionmentioning
confidence: 52%
“…Forty-nine SSR markers distributed along 8 linkage groups of the Prunus reference map were used for genotyping ( Table S2). The SSRs that were used were similar to those in previous studies (Aranzana et al, 2010;Li et al, 2013). Polymerase chain reaction (PCR) amplifications were carried out as described by Aranzana et al (2003) using fluorescence-labeled primers.…”
Section: Dna Isolation and Ssr Amplificationmentioning
confidence: 99%
“…Old varieties from Japan had the genetic background of Shanhai Suimitsuto (Yamamoto et al, 2003). However, genetic relationships, backgrounds, and evolution of local cultivars in China have not been emphasized in the previous studies (Cao et al, 2012;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peach is becoming a very promising climacteric drupe model to enhance our insight into ethylene biology and ripening, and for genomic analysis of fruit tree species (Li et al 2013;Verde et al 2013), even though transformation events in peach have been rarely reported (Pérez-Clemente et al 2004). Like other fruit species, stress restricts the yield and geographical area over which peach trees can be planted, and this continues to drive worldwide efforts to generate stress-tolerant cultivars using traditional and molecular genetic approaches ).…”
mentioning
confidence: 99%